The effect of open-wedge and closed-wedge high tibial osteotomies on the tibial posterior slope—a study of two hundred seventy-nine cases - Schubert, Ilona; Ferner, Felix; Dickschas, Jörg (International Orthopaedics, 2020)
Purpose: There are two established techniques for high tibial valgisation osteotomy (HTO): medial open wedge (MOW) and lateral closed wedge (LCW). The aim was to analyze the change of the posterior tibial slope (PTS) caused by HTOs dependent on the technique. Methods: Four hundred fourteen cases of HTOs were analyzed retrospectively. Two hundred seventy-nine osteotomies in 247 patients matched the inclusion criteria and were divided into two treatment groups (MOW/LCW). The PTS was determined on pre- and post-surgical lateral knee X-rays by measuring the proximal posterior tibial angle (PPTA). Results: One hundred ninety of the included 279 cases were assigned to the MOW and 89 to the LCW group. The mean PPTA in MOW HTOs was 79.9° ± 32° (68–88°) and in LCW HTOs 80.6° ± 2.6° (74–88°). There was no statistically significant change of the PPTA in the MOW group comparing the pre- and post-surgical values (delta PPTA 0.07° ±2.9° (− 12 to 11°)). In the LCW group, the surgery resulted in a statistically significant reduction (p< 0.001) of the PTS (delta PPTA − 3.09° ± 4.5° (− 12 to 5°)). Conclusion: The important finding of this study is that the thesis of a slope increase in MOW osteotomies found in the literature could not be approved regarding our results as no statistically significant change of PTS in MOW HTOs was observed. The findings support the common thesis that LCW osteotomies cause a slope reduction.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Lateral closed wedge osteotomy (LCW); Medial open wedge osteotomy (MOW); Posterior tibial slope